PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN: (Studi Kasus di Galeri Jenang Kelapa Sari Rejowinangun Blitar) - Lu’lu Ul Maknunah; Rika Dwi Apriliyaningsih (Universitas Islam Balitar, 2020)
UD. Kelapa Sari Blitar is an individual company founded by Mr. H. Imam Muhtadi engaged in production. The price level applied by the company affects the quantity sold. In addition, indirectly the price also affects costs, because the quantity sold affects the costs incurred in relation to production efficiency. A very important factor in purchasing decisions is the price setting goals. Prices have an impact on financial performance and have an important effect on the value of brand positioning in the minds of customers. The purpose of this study is to find out how the effect of prices on purchase decisions at UD. Kelapa Sari Rejowinangun Blitar. The population in this study were all buyers who had bought at UD. Sari Sari Rejowinangun Blitar. Samples in this study amounted to 84 respondents. The sampling collection technique used in this study was incidental sampling. The method of collecting data in this study was using questionnaires, literature, and documentation. From the results of research and discussion it can be concluded that the price (X) does not affect the purchase decision (Y) at UD. Kelapa Sari Blitar.